2021
DOI: 10.3390/foods10040767
|View full text |Cite
|
Sign up to set email alerts
|

“The Good, The Bad, and the Minimum Tolerable”: Exploring Expectations of Institutional Food

Abstract: There is a tendency towards greater expectations of consumer goods and services in society—what was once judged as ideal may now be a bare minimum. This presents a challenge for food providers in the upcoming decades. As the more demanding baby boomer cohort ages, health institutions of the future will face challenges meeting their food expectations. The purpose of this study was to explore expectation type dynamics and function with updated empirical material on aging consumers expectations of institutional f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…It may be assumed that they do not have any specific expectations associated with food products, as the major value of food for them is associated with satisfying their hunger, rather than palatability and pleasure of consumption, but this approach is rare [ 39 ]. It may result from the fact that they have neither positive nor negative expectations associated with food products, but they have neutral expectations associated with choosing minimally tolerable products as good enough for them [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may be assumed that they do not have any specific expectations associated with food products, as the major value of food for them is associated with satisfying their hunger, rather than palatability and pleasure of consumption, but this approach is rare [ 39 ]. It may result from the fact that they have neither positive nor negative expectations associated with food products, but they have neutral expectations associated with choosing minimally tolerable products as good enough for them [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can help to understand their food choices, which can satisfy consumers needs and provide food companies with a competitive advantage. More and more researchers have realized this [ 30 , 31 , 32 , 33 ]. For example, Zhang et al [ 34 ] conducted an online survey for dwellers in 489 cities in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study focuses on classifying baby boomers based on individual characteristics, which, according to previous research, could contribute to higher expectations of this ageing population (Gill and Cameron, 2020;Sudbury-Riley et al, 2015). A preliminary study presented at the Society for Consumer Psychology Conference in 2021 (Andreassen et al, 2021a) revealed that individual characteristics influence expectations of institutional food. The current article explores whether meaningful clusters that allow us to understand different segments of ageing consumers can explain these expectations.…”
Section: Various Segments Of Ageing Consumersmentioning
confidence: 99%
“…Currently, knowledge about ageing consumers' expectations of institutional food and health services is limited, and more future-oriented studies are needed (Andreassen et al, 2021b;Gill and Cameron, 2020;Quine and Carter, 2006). Notwithstanding, ageing consumers have generally received scant attention in consumer research and have often been treated as a homogeneous group (Lumpkin, 1985).…”
Section: Introductionmentioning
confidence: 99%